Setting up self-help groups in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A government extension programme in Nigeria is helping young people to set up self-help groups. Through these young people become engaged in a variety of income-generating activities, including agriculture and food processing. The report includes comments from a member of the extension service, and one of the group members.